An Activation Likelihood Estimation Meta-Analysis of Specific Functional Alterations in Dorsal Attention Network in Mild Cognitive Impairment - Wu, Huimin; Song, Yu; Chen, Shanshan; Ge, Honglin; Yan, Zheng; Qi, Wenzhang; Yuan, Qianqian; Liang, Xuhong; Lin, Xingjian; Chen, Jiu (Frontiers in Neuroscience, 2022)
Background: Mild cognitive impairment (MCI) is known as the prodromal stage of the Alzheimer’s disease (AD) spectrum. Recent studies have advised that functional alterations in the dorsal attention network (DAN) could be used as a sensitive marker to forecast the progression from MCI to AD. Therefore, our aim was to investigate specific functional alterations in the DAN in MCI. Methods: We systematically searched PubMed, Embase and Web of Science and chose relevant articles based on three functional indicators, the amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo) and functional connectivity (FC) in the DAN in MCI. Based on the activation likelihood estimation, we accomplished the aggregation of specific coordinates and the analysis of functional alterations. Results: A total of 38 studies were involved in our meta-analysis. By summing up included articles, we acquired specific brain region alterations in the DAN mainly in the superior temporal gyrus (STG), middle temporal gyrus (MTG), superior frontal gyrus (SFG), middle frontal gyrus (MFG), inferior frontal gyrus (IFG), precentral gyrus (preCG), inferior parietal lobule (IPL), superior parietal lobule (SPL). At the same time, the key area showing anti-interaction with default mode network included the IPL in the DAN. The one showing interactions with executive control network was mainly in the MFG. Lastly, the frontoparietal network showed a close connection with DAN especially in the IPL and IFG. Conclusion: This study demonstrated abnormal functional markers in the DAN and its interactions with other networks in MCI group respectively. It provided the foundation for future targeted interventions in preventing the progression of MCI.